Barriers And Benefits Of Adopting E-Government In Iran - Amjad, Leila Saeidi (2010)
This thesis investigate the insight problems of e-government implementation in Iran and the benefits for the development of the country from user point of view. The method used is to scrutinise the perception of users that directly influence their willingness to use.